A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP N I PERANAP IN COMPREHENDING NARRATIVE TEXTS - Syaputra, Yopieka Syaputra; Ras, Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study is to find out the second year students’ ability of SMPN 1 Peranap in comprehending narrative texts. This research focuses on finding factual information, finding main ideas, locating the meaning of vocabulary in context, identifying references, and making inferences based on recount texts. Data were collected using reading comprehension test with multiple choice type. The test contained 30 items. The try out was conducted to check the validity and reability of the test. The research findings are as follows: first, the ability of the students in comprehending narrative text, from 30 students, In terms of finding factual information, from 30 students, 18 students (45%) are in excellent level, 11 students (27.5%) are in good level, 1 student (2.5%) is in mediocre level. In term of finding main idea, 15 students (37.5%) are in excellent level, 12 students (30%) are in good level, 3 students (5%) are in mediocre level. In term meaning of vocabulary, 12 students (30%) are in excellent level, 13 students (32.5%) are in good level, 4 students (10%) are in mediocre level. And 1 student (2.5%) is in poor level. In term of identifying reference, 3 students (7.5%) are in excellent level, 10 students (25%) are in good level, 15 students (37.5%) are in mediocre level. And 2 students (5%) are in poor level. In term of finding the inference, 2 students (5%) are in excellent level, 7 students (17.5%) are in good level, 12 students (30%) are in mediocre level. 7 students (17.5%) are in poor level. And 2 students (5%) are in very poor level. Keywords:Ability, Comprehending, Narrative Texts.